Magnetohydrodynamic Free Stream and Heat Transfer of Nanofluid Flow Over an Exponentially Radiating Stretching Sheet With Variable Fluid Properties - Irfan, Muhammad; Farooq, Muhammad Asif; Iqra, Tousif (Frontiers in Physics, 2019)
This article deals with the nanofluid flow and heat transfer of the MHD free stream over an exponentially radiating stretching sheet accompanied by constant and variable fluid characteristics together. The underlying governing partial differential equations (PDEs) have been translated into nonlinear ordinary differential equations (ODEs) by incorporating adequate similarity transformations. By using the shooting method and the MATLAB built-in solver bvp4c, the corresponding ODEs are effectively solved. The impact on the skin friction coefficient (quantifying resistance), the local Nusselt number (heat transfer rate) and the local Sherwood number (mass transfer rate) on the surface due to the flow field variables has been computed against various parameters i.e., magnetic parameter M, Prandtl number Pro, Lewis number Le, thermophoresis parameter Nt, Brownian motion parameter Nb, velocity parameter λ, radiation parameter Rd and thermal conductivity parameter ϵ. Graphs are also plotted to study the impact of distinct parameters on velocity, temperature and concentration profiles. It has been noted by raising the values of ϵ, the heat transfer rate reduces for variable fluid properties. On the other hand, raising Pro increases the heat transfer rate.